EFEKTIVITAS PENGHAPUSAN KEWAJIBAN JUSTICE COLLABORATOR SEBAGAI SYARAT PEROLEHAN HAK PEMBEBASAN BERSYARAT BAGI NARAPIDANA TINDAK PIDANA NARKOTIKA (Studi Kasus Pada Lembaga Pemasyarakatan Kelas II A Karawang) - Dahrul Manalu; Deny Guntara; Muhamad Abas (Peneliti.net, 2023)
Penitentiary is a place where convicts serve their sentence. Prisoners become fostered citizens so that their lives are better. Activities in Correctional Institutions are based on applicable legal provisions. The effectiveness of coaching in Correctional Institutions is influenced by the power of law. The law governing convicts in correctional institutions is Permenkumham Number 7 of 2022. Broadly speaking, these regulations regulate procedures for granting remissions, assimilation, leave to visit family, parole, leave before release and leave on parole. The regulation also contains the abolition of Justice Collaborators as a condition for obtaining parole rights for convicts of narcotics crimes. This study aims to find out the reasons for the removal of Justice Collaborators against convicts of narcotics crimes and to determine the effectiveness of the removal of Justice Collaborators as a condition for obtaining parole rights for convicts of narcotics crimes in Karawang Penitentiary. This research is an empirical research using qualitative research methods with an empirical juridical approach. According to the Karawang Penitentiary, the removal of the Justice Collaborator as a condition for obtaining parole for narcotics convicts has had a good impact and made it easier for narcotics convicts to apply for parole.